Orthodox Christianity facing the challenges of fluidity of identity - Matić, Zlatko (Bogoslovni vestnik, 2025)
The aim of this paper is to examine the issue of Christian identity, i.e. the identity of the Church in modern pluralistic society which is described using the terms of “fluidity,” “liquidity” and overcoming of all stable categorical definitions of individuals or social structures. The author describes this world as a positive stimulus for the Church which is obliged to re-examine some inherited theological assumptions of the strong (ontologized) identity and attempt to understand its position in the world where only uncertainty is certain, only insecurity is secure and only the state of continuous change is unchangeable. In this manner, the modern socio-political and religiological situation in the world would significantly contribute to overcoming certain ecclesiological limitations of modern theological thought (nationalist predispositions, the problem of the ecclesial identity of others, etc.).
Keywords: Bauman, Zygmunt; fluid identities; fluidne identitete; globalism; globalizem; identiteta Cerkve; identity of the Church; pluralism; pluralizem